Information from pharmaceutical companies and the quality, quantity, and cost of physicians' prescribing: a systematic review - Spurling, Geoffrey K.; Mansfield, Peter R.; Montgomery, Brett D.; Lexchin, Joel; Doust, Jenny; Othman, Noordin; Vitry, Agnes I. (Public Library of Science, 2010)
Background Pharmaceutical companies spent $57.5 billion on pharmaceutical promotion in the United States in 2004. The industry claims that promotion provides scientific and educational information to physicians. While some evidence indicates that promotion may adversely influence prescribing, physicians hold a wide range of views about pharmaceutical promotion. The objective of this review is to examine the relationship between exposure to information from pharmaceutical companies and the quality, quantity, and cost of physicians' prescribing. Methods and Findings